Pendidikan Islam Berbasis Kisah: Nilai Pendidikan Islam dalam Sirah Nabi - Syaefudin Achmad (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
The purpose of this study is to analyze the values of Islamic education in the life story of the Prophet Muhammad. The story contains lessons, morals, and values for all humans. The storytelling technique is very effective in attracting students to listen to a story. Students can imitate good characters and not imitate bad ones. The story of the Prophet Muhammad contains many values of Islamic education that can be imitated by students. Students are expected to imitate the morals of the Prophet Muhammad after listening to his story. This research is library research with the data source in the form of a manuscript containing the story of the Prophet Muhammad. This research uses documentation data collection techniques as well as inductive data analysis. The findings of this study show that there are values of Islamic education in the story of the Prophet Muhammad, including the values of hardworking, fair, patient, humble, honest, forgiving, and trustworthy.